Communication in times of trouble : best practices for crisis and emergency risk communication - Seeger, Matthew W 1957- (Wiley Blackwell, 2019)
"This book expands the focus by taking a 'best practices' approach to crisis communication and emergency risk communication, including an extensive discussion of how risks are identified and managed as part of crisis planning and recovery, as well as audience analysis, pre- and long-term post-crisis recovery, and the return to risk assessment and crisis planning. In addition, the added focus on emergencies, those threatening events that happen with greater frequency than full-blown crises, makes this book more appealing for practitioners than a book dedicated solely to crisis communication. Moreover, the added focus on emergencies includes naturally occurring events such as earthquakes, tornadoes, hurricanes, tsunamis, epidemics, and pandemics. In existing crisis communication texts, these events are generally not covered in detail"--